Antipsychotic prescribing practices and patient, family member and healthcare professional perceptions of antipsychotic prescribing in acute care settings: a scoping review protocol - Zahinoor Ismail; Daniel Niven; Kirsten Fiest; Lisa Burry; Karla D Krewulak; Natalia Jaworska; Stephana Julia Moss; Zara Stelfox (BMJ Open)
Introduction Antipsychotic medications are commonly prescribed off-label in acutely ill patients for non-psychiatric clinical indications such as delirium or insomnia. New prescription initiation of antipsychotics in acute care settings increases the proportion of patients discharged home on antipsychotics without approved clinical indication. Long-term use of antipsychotics is associated with increased risk of sudden cardiac death, falls and cognitive impairment. An understanding of acute care off-label antipsychotic prescribing practices and healthcare professional, patient and family perceptions related to antipsychotic prescribing and deprescribing is necessary to facilitate in-hospital deprescribing initiatives.Methods and analysis We present the protocol for a scoping review following the methodology proposed by Arksey and O’Malley and the Scoping Review Methods Manual by the Joanna Briggs Institute. We will search five databases including MEDLINE, EMBASE, CINAHL, PsycINFO and Web of Science from inception to 3 July 2021 (ie, planned search date). We will include both peer-reviewed and non-peer-reviewed qualitative and quantitative studies to identify antipsychotic prescribing practices, and to describe healthcare professional, patient and family perceptions towards antipsychotic prescribing and deprescribing in the acute care setting. Protocols, systematic and scoping reviews will be excluded. Two reviewers will calibrate and perform study screening and data abstraction for quantitative and qualitative outcomes of eligible studies. Quantitative outcomes will include study identifiers, demographics and descriptive statistics of antipsychotic prescribing practices. Qualitative synthesis describing perceptions on antipsychotic prescribing practices will include deductive thematic analysis with mapping of themes to the domains of the Theoretical Domains Framework, a 14-domain behaviour and behaviour change framework.Ethics and dissemination No ethical approval will be required for this study as only data from published studies in which informed consent was obtained by primary investigators will be retrieved and analysed. The results of this scoping review will inform integrated knowledge translation initiatives aimed at in-hospital antipsychotic medication deprescribing.